DETEKSI DINI DAN PENANGANAN FAKTOR RISIKO PENYAKIT KARDIOVASKULAR PADA PENDUDUK USIA 45 TAHUN KE ATAS DI DESA PEGAYAMAN BULELENG - I.A, Ika Wahyuniari; I.G.A, Dewi Ratnayanti; G.N, Mayun; G.N, Sri Wiryawan; N.M, Linawati; W, Sugiritama (Buletin Udayana Mengabdi, 2012)
Cardiovascular diseases such as heart attacks and strokes, are the main cause of death in Indonesia. Information about risk factors of these disease (like hypertension, diabetes mellitus, obesity) are required in order to control and prevent the disorders. The aim of this program was at early detection and managing the relevant risk factors. The program commenced by providing information about risk factors of cardiovascular disease and by examining the level of blood pressure, blood sugar, body weight, body height, and waist circumference. Participants that have risk factors of cardiovascular disease in Pagayaman were 52,94%. Most of them had abnormal waist circumference (59,26%), particularly in woman. The next and most prevalent risk factors were Body Mass Index (40,74%), hypertension (18,52%), and hyperglycemia (3,70%).